The Effectiveness of Behavioral Group Counseling with Self-Management and Reinforcement Techniques to Reduce Students’ Truancy (Jurnal Bimbingan Konseling, 2020)
This study aimed at examining the influence of behavioral group counseling with self-management and reinforcement techniques to reduce the truancy of MA Assalafiyah Luwunggragi Brebes students. To do so, there were 16 students from class XI involved as the subjects of the study. These students were divided into two groups, namely one group with the treatment of self-management technique, and another group with the treatment of reinforcement technique. For more, the sampling technique used by the researchers was purposive sampling. It was done by inspecting students’ attendance list from school counselors. The results showed that there was there was a decrease in students’ truancy after receiving behavioral group counseling with self-management and management techniques. Based on these findings, counselors are suggested to apply behavioral group counseling with self-management and reinforcement techniques to reduce students’ truancy.